Moving from autonomous to planned adaptation in the montane forests of southeastern Australia under changing fire regimes. (14th September 2016) - Doherty, Michael D.; Lavorel, Sandra; Colloff, Matthew J.; Williams, Kristen J.; Williams, Richard J.
Abstract: Forest ecosystems and their associated natural, cultural and economic values are highly vulnerable to climate driven changes in fire regimes. A detailed knowledge of forest ecosystem responses to altered fire regimes is a necessary underpinning to inform options for adaptive responses under climate change, as well as for providing a basis for understanding how patterns of distribution of vegetation communities that comprise montane forest ecosystems may change in the future. Unplanned consequential adaptation of both natural and human systems, i.e. autonomous adaptation, will occur without planned intervention, with potentially negative impacts on ecosystem services. The persistence of forest stands under changing fire regimes and the maintenance of the ecosystem services that they provide pivot upon underlying response traits, such as the ability to resprout, that determine the degree to which composition, structure and function are likely to change. The integration of ecosystem dynamics into conceptual models and their use in exploring adaptation pathways provides options for policy makers and managers to move from autonomous to planned adaptation responses. Understanding where autonomous adaptation provides a benefit and where it proves potentially undesirable is essential to inform adaptation choices. Plausible scenarios of ecological change can be developed to improve an understanding of the nature and timing of interventions and their consequences, well before natural and human systems autonomously adapt in ways that may be detrimental to the long‐term provision of ecosystem services. We explore the utility of this approach using examples from temperate montane forest ecosystems of southeastern Australia.